How does remote work affect the performance and flow of supply chain management : Case critical communications organization - Heikkinen, Ville Thomas (My University, 2022)
The COVID-19 pandemic disrupted various industries globally and organizations and individuals had to adapt to the situation. Due to safety measures and restrictions, lockdowns were placed, and the employees shifted to work remotely almost overnight. Supply shortages became a challenge which affected various industries when the demand grew exponentially for some items during the pandemic. Furthermore, investments in digital tools and processes were implemented and supply chain performance are evaluated in detail. The purpose of this thesis is to analyze how working from home affects the employees’ productivity and their performance from the perspective of the employees and the organization. Furthermore, to analyze how has remote work affected the performance of the supply chain in the case company. Research methods utilized in this thesis are relevant academic literature, qualitative research that includes openly questioned interviews with the case company’s employees and secondary data from internal reports. These were analyzed to answer the research questions and combined for coherent and extensive research. In conclusion, working from home affected positively the performance from the perspective of the employees and the organization. They performed better in some tasks that required deep concentration and the targets were met by the employees. However, the communication between employees decreased remotely, and some knowledge isn’t shared. It forms bottlenecks in the supply chain. In addition, this creates challenges in decision-making for managers. From the organization’s side, it was beneficial and economically cost-saving. People performed better, the organization could save expenses and people took fewer sick days. In addition, employees felt trusted, and they valued the possibility to choose the preferred work method. Remote work affected positively the supply chain as employees performed better and fewer delivery errors and late deliveries were caused by the employees remotely. However, the supply chain performance decreased due to suppliers being late and because of missing materials. Therefore, these weren’t related to employees in the case organization working remotely, but due to the global supply shortage. The results of this study can be utilized for the management in their decision-making to evaluate what kind of working methods are preferred in the future. Remote work creates challenges for social interactions and for creating a bond and commitment to the organization, especially for newcomers in the organization. These are challenges that must be evaluated, and actions must be made to ensure that employees feel valued.
Keywords: supply chains; remote work; employees; logistics; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management; Logistics and Production Operations Management